Exile, the Malvinas War and human rights - Jensen, Silvina Inés (2021)
In Historia reciente: Perspectivas y desafíos de un campo en construcción, Marina Franco and Florencia Levín signal one of the most pertinent challenges for researchers working on the Malvinas today: the need to develop conceptual precision (2007, p. 58). Through precision, they argue, we might free our analytical categories from both their status as value judgements and from the powerful connotations generated by the protagonists of a recent conflict-filled past, in the hope that research might avoid reproducing the political battles that these categories entail...